PROSPECTS OF BIODIESEL PRODUCTION FROM FOOD CROPS IN LAGOS, NIGERIA - HUMPHREY, IBIFUBARA; OBOT, I. Nsikan; OLUGBON, Busola; OYEBOLA, O. Olusola (Covenant Journal of Physical and Life Sciences, 2023)
The energy crisis in Nigeria is still severe and persistent due to the country’s expanding population and the resulting rise in energy consumption, as well as its underdeveloped electrical energy infrastructure and the massive issues with conventional energy sources such as continual gas flaring. This research compares the quality of various biodiesel blends made from various vegetable oils. Through a transesterification reaction, biodiesel was made from animal fat oil and bleached palm, corn, cottonseed, peanut, and soya oils. Four blends’ (B20, B50, B80 and B100) physiochemical characteristics were measured to check for compliance in accordance with the ASTM standard for biodiesel. The results show that the bulk of the feedstock has a high percentage yield, with bleached palm oil having the highest yield (95%), and animal fat having the lowest yield (61.5%). Viscosity was measured at temperatures ranging from 10°C to 60°C, with animal fat B100 having the highest value (7.717 mm2/sec) at 10°C and corn oil B20 having the lowest value (1.840 mm2/sec) at 60°C. Furthermore, the sulfur content, flash point, density, and cold point readings were all within the ASTM standard range.